Corporate taxes in the world economy: reforming the taxation of cross-border income - Harry Grubert; Rosanne Altshuler (Rutgers University, Department of Economics, 2006)
Proposals for the reform of the taxation of cross-border income are evaluated within the general context of the corporate tax in an open economy. We focus on the various behavioral decisions that can be affected such as the location of income and its repatriation. The two income tax proposals considered are: (1) dividend exemption and (2) burden neutral worldwide taxation in which all foreign subsidiary income is included currently in the U.S. worldwide tax base, and at the same time the corporate tax rate is lowered and overhead allocations to foreign income are eliminated so as to keep the overall U.S. tax burden on foreign income the same. We also consider the attractiveness of destination-based and origin-based consumption taxes. Our evaluation of reform options makes use of the best available information. We also present new information on the burden of the current system. However, there are many important unknown behavioral parameters required to judge international tax systems and this missing information, some of which may ultimately be unknowable, makes it difficult to make definitive recommendations. The burden neutral worldwide option seems to offer greater efficiency gains among the two income tax options, particularly because of reduced incentives for income shifting which wastes resources and distorts effective tax rates on investment. To be sure, the burden neutral worldwide option would increase effective tax rates on investment in low-tax countries while not increasing the average U.S. tax rate on foreign source income. The option requires a substantial reduction in the U.S. corporate tax rate. We suggest that increased capital mobility makes changing the mix of corporate and personal level taxation of business income appropriate even apart from the special issues of cross-border taxation such as repatriation taxes and income shifting opportunities that are the main subject of the paper.
Keywords: H20; 330; International taxation; multinational corporations; tax reform